46 The Sympathetic Nervous System In Tendinopathy – A Systematic Review. (5th September 2014) - Jewson, Jacob L; Lambert, Gavin W; Storr, Michael; Gaida, James E
Abstract : Introduction: The pathophysiology of tendon pain is not fully understood, although preliminary data indicates involvement of the sympathetic nervous system (SNS). Large prospective studies identify sympathetic drive as a risk factor for development of metabolic conditions such as insulin resistance/type 2 diabetes mellitus. Therefore, SNS activity may underpin the association between metabolic factors and tendinopathy in sedentary populations. The objective of this systematic review was to examine the role of the SNS in human tendinopathy. Methods: Published data describing sympathetic innervation or an index of sympathetic activity in a human tendon were eligible for inclusion. Bibliographical databases (AMED, Biological Abstracts, CINAHL Plus, EMBASE, MEDLINE, Scopus, SPORTDiscus and Web of Science) were searched for relevant articles. Reference lists from included articles were screened for additional articles. Studies were scored with a quality assessment tool to identify potential sources of bias. Each question had an explicit decision rule to guide assessment. Meta-analysis was performed on studies that gave appropriate statistical data. Results: Nine case-control and 4 cross-sectional studies examined sympathetic innervation of tendons via biopsies. Sympathetic markers were found through immunohistochemistry (e.g. tyrosine hydroxylase (TH), neuropeptide Y or adrenoreceptors) or through in situ hybridisation (e.g. TH mRNA). There was evidence to suggest a lack of difference in SNS innervation of the tendon proper between painful and non-painful tendons. In contrast, the paratendinous tissue showed evidence of increased SNS innervation in painful tendons. The most notable increase in SNS markers was seen in abnormal tenocytes from painful tendons. Data from two studies were suitable for meta-analysis (fig 1 ). 3, 4 These heterogeneous studies revealed no difference in SNS innervation between painful and pain-free tendons when analysed together due to the different tissues being sampled (i.e. tendon proper vs. paratendinous tissue). No studies recorded SNS activity in vivo. Discussion: Sympathetic innervation in tendinopathy appears to be dependent on the type of tissue being sampled. The findings in the tendon proper suggest that the SNS is not upregulated in tendinopathy. Findings of increased SNS in the paratendinous tissue are particularly relevant, as this tissue has been a target of new arthroscopic surgical therapies. The consistent change seen in tenocytes suggested that abnormal cells had an increased capacity to self-produce catecholamines, inferring a possible positive feedback loop with the SNS. Studies were limited by difficulty recruiting healthy controls and there was a limited quantitative data (demonstrated by the meta-analysis). Measuring global sympathetic activity in vivo will be an important area for future tendinopathy research. References: 1 Flaa et al . Metabolism: Clinical and Experimental. 2008;57(10):1422–7 2 Gaida et al . Medicine and Science in Sports and Exercise. 2009;41(6):1194–7 3 Lian et al . American Journal of Sports Medicine. 2006;34(11):1801–8 4 Sasaki et al . Journal of Orthopaedic Scienc. 2013.18(4):528–35